Solve the following pair of linear equation by elimination method
1) 3x - 5y - 4 = 0
9x = 2y + 7
2) x/2 + 2y/3 = -1
x - y/3 = 3
Answers
here is your answer:-
==================================
given,
3x - 5y - 4 = 0
9x = 2y + 7
now,
3x - 5y - 4 = 0--------(1)
9x = 2y + 7
=> 9x - 2y - 7 = 0 -----------(2)
(1) × 3 => 9x - 15y - 12 = 0 --------(3)
(2) × 1 => 9x - 2y - 7 = 0 ----------(4)
_____________________________
(3) - (4) => - 13y - 5 = 0
=> - 13y - 5 = 0
=> - 13y = 5
=> y = -5/13
value of y put in (1)
3x - 5 ( - 5/13 ) - 4 = 0
=> 3x + 25/13 - 4 = 0
=> 3x = 4 - 25/13
=> 3x = 52 - 25/13
=> 3x = 27/13
=> x = 27/13 × 1/3
=> x = 9/13
.°. x = 9/13 , y = - 5/13☺
===================================
2)
x/2 + 2y/3 = - 1
=> 3x + 4y/6 = - 1
=> 3x + 4y = - 6-------------(1)
x - y/3 = 3
=> 3x - y/3 = 3
=> 3x - y = 9 ----------(2)
(1) - (2) => 3x + 4y = - 6
3x - y = 9
____________________________
5y = - 15
=> y = - 3
now value of y put in ( 1)
3x + 4 ( - 3 ) = - 6
=> 3x - 12 = - 6
=> 3x = - 6 + 12
=> 3x = 6
=> x = 6/3 = 2
.°. x = 2, y = - 3☺
====================================
Brainly User
Hi ☺
here is your answer:-
==================================
given,
3x - 5y - 4 = 0
9x = 2y + 7
now,
3x - 5y - 4 = 0--------(1)
9x = 2y + 7
=> 9x - 2y - 7 = 0 -----------(2)
(1) × 3 => 9x - 15y - 12 = 0 --------(3)
(2) × 1 => 9x - 2y - 7 = 0 ----------(4)
_____________________________
(3) - (4) => - 13y - 5 = 0
=> - 13y - 5 = 0
=> - 13y = 5
=> y = -5/13
value of y put in (1)
3x - 5 ( - 5/13 ) - 4 = 0
=> 3x + 25/13 - 4 = 0
=> 3x = 4 - 25/13
=> 3x = 52 - 25/13
=> 3x = 27/13
=> x = 27/13 × 1/3
=> x = 9/13
.°. x = 9/13 , y = - 5/13☺
===================================
2)
x/2 + 2y/3 = - 1
=> 3x + 4y/6 = - 1
=> 3x + 4y = - 6-------------(1)
x - y/3 = 3
=> 3x - y/3 = 3
=> 3x - y = 9 ----------(2)
(1) - (2) => 3x + 4y = - 6
3x - y = 9
____________________________
5y = - 15
=> y = - 3
now value of y put in ( 1)
3x + 4 ( - 3 ) = - 6
=> 3x - 12 = - 6
=> 3x = - 6 + 12
=> 3x = 6
=> x = 6/3 = 2
.°. x = 2, y = - 3☺
====================================